2003
DOI: 10.1021/ac020695h
|View full text |Cite
|
Sign up to set email alerts
|

UV Vapor Generation for Determination of Selenium by Heated Quartz Tube Atomic Absorption Spectrometry

Abstract: A new vapor generation technique utilizing UV irradiation coupled with atomic absorption for the determination of selenium in aqueous solutions is described. In the presence of low molecular weight organic acid solutions, inorganic selenium(IV) is converted by UV irradiation to volatile selenium species, which are then rapidly transported to a heated quartz tube atomizer for detection by atomic absorption spectrometry. Optimum conditions for photochemical vapor generation and interferences from concomitant ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
195
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(207 citation statements)
references
References 22 publications
11
195
0
1
Order By: Relevance
“…Guo et al [17] reported no interference from the presence of 500 mg L -1 Ni 2+ and 100 mg L -1 Co 2+ during PVG of selenium. However, in the presence of 10 mg L -1 Ni 2+ or Co 2+ , serious signal suppression is encountered for its conventional hydride generation [18].…”
Section: Interferences Whereas a Major Shortcoming Associated With Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [17] reported no interference from the presence of 500 mg L -1 Ni 2+ and 100 mg L -1 Co 2+ during PVG of selenium. However, in the presence of 10 mg L -1 Ni 2+ or Co 2+ , serious signal suppression is encountered for its conventional hydride generation [18].…”
Section: Interferences Whereas a Major Shortcoming Associated With Cmentioning
confidence: 99%
“…This likely arises because they are able to preferentially scavenge (react with) the UVgenerated organic radicals. A further possibility is that the reduced Se or Te species may form an alloy or co-precipitate as a colloid [17] with the free iron atom intermediates generated during PVG. Such effects may potentially be eliminated or minimized when rapid separation of volatile Se or Te species from the liquid phase can be accomplished.…”
Section: Interferences Whereas a Major Shortcoming Associated With Cmentioning
confidence: 99%
“…In the past years, photo-induced reduction or CVG was reported as a technique for remediation of heavy metal contamination [16][17][18][19]. This chemical vapour generation, in presence of organic acid under UV irradiation, was also coupled with atomic spectrometry for the analysis of selenium, mercury and other metal or non-metal element [20,21], which proved that the green, simple and selective UV-CVG is a useful new alternative to the conventional KBH 4 system. Further, a UV/nano-TiO 2 vapour generation device with formic acid was adopted for coupling HPLC with ICP-MS for the determination of inorganic Se(IV) and Se(VI) [22].…”
Section: Introductionmentioning
confidence: 97%
“…Guo et al [41] first introduced PVG in 2003, and applications of this new sample introduction quickly expanded [42,43]. A wide range of elements can be photochemically derivatized to volatile species, such as Hg [44,45], Ni [46,47], Se [43], Co [48,49], Fe [50], and I [51,52].…”
Section: Photochemical Vapor Generation Systemsmentioning
confidence: 99%